The Immune Response to Trypanosoma cruzi: Role of Toll-Like Receptors and Perspectives for Vaccine Development. (16th February 2012) - Rodrigues, Mauricio M.; Oliveira, Ana Carolina; Bellio, Maria
Abstract : In the past ten years, studies have shown the recognition of Trypanosoma cruzi -associated molecular patterns by members of the Toll-like receptor (TLR) family and demonstrated the crucial participation of different TLRs during the experimental infection with this parasite. In the present review, we will focus on the role of TLR-activated pathways in the modulation of both innate and acquired immune responses to T. cruzi infection, as well as discuss the state of the art of vaccine research and development against the causative agent of Chagas disease (or American trypanosomiasis).